Encaixando as peças de um mosaico: multifuncionalidade e economia ecológica para estudos sobre pesca artesanal. - Cajado, Diana Mendes (2019)
The structure of this thesis was inspired by the proposal of a mosaic, so that the chapters, although in themselves, constitute results, behave like pieces that are embedded in the last chapter with the innovative intention of proposing a methodological "design" totalizing for studies on artisanal fishing, from the category of analysis Multifunctionality and the paradigm of the Ecological Economy (EE). This format is motivated by the need to deepen the understanding of the complex structure that makes up the artisanal fishing, so that the orienting questions emanate from empirical, theoretical and bibliographic paths. The research was anchored in the questions: how is the production of knowledge related to artisanal fishing and Multifunctionality organized? How can the analytical category Multifunctionality of agriculture contribute to an understanding of the functions of artisanal fisheries? What are the conditions for these functions to manifest? Do the inherent functions of artisanal fisheries find their possibilities of manifestation in the Ecological Economy? Which methodological path can be suggested for studies that intend to understand the multifunctional artisanal fishing from the paradigms of the Ecological Economy? Chapter I is responsible for carrying out a bibliographic survey of scientific production on artisanal fisheries, Multifunctionality and Ecological Economics, being a key piece for the dimensioning of the research presented here. Chapter II presents a review study on Multifunctionality, identifying the possibilities of incorporating this category into studies in artisanal fisheries. In chapter III it brings the paradigm of the Ecological Economy comparing it to the Neoclassical Economy like distinct proposals for the fishing activity. Finally, in chapter IV presents the methodological proposal for studies in artisanal fishing, assuming EE as oikos of this way of life.